Experimental study on active seismic isolation using interferometric inertial sensors. (November 2020) - Zhao, G.; Ding, B.; Watchi, J.; Deraemaeker, A.; Collette, C.
Highlights: A homemade interferometric uniaxial inertial sensor is developed. Tilt-vertical coupling of the sensor is studied. The potential for active seismic isolation is experimentally examined. Abstract: The goal of this study is to demonstrate the capability to actively isolate a platform from seismic vibrations using an interferometric inertial sensor. To this purpose, a homemade high-resolution interferometric uni-axial inertial sensor (in the vertical direction) is developed and then integrated to a single-degree-of-freedom (SDOF) seismic isolation system. A theoretical study is firstly performed in order to better understand the dynamics of the system. It is found that the sensor suffers from a tilt-vertical coupling due to the influence of the gravity force if the sensor is not perfectly aligned. By taking this tilt coupling into account, a dedicated controller is designed, seeking a large vibration isolation in the frequency band of interest. Experiments are then conducted for validating the theoretical analysis and examining the vibration isolation performance. It shows a reduction of the transmitted motion of up to 60 dB in a frequency range from 0.1 Hz to 10 Hz.